Non-Enzymatic Functions of Retroviral Integrase: The Next Target for Novel Anti-HIV Drug Development - Masuda, Takao (Frontiers in Microbiology, 2011)
Integrase (IN) is a retroviral enzyme that catalyzes the insertion of viral DNA into host chromosomal DNA, which is necessary for efficient viral replication. The crystal structure of prototype foamy virus IN bound to cognate viral DNA ends, a complex referred to as the intasome, has recently been resolved. Structure analysis of the intasome revealed a tetramer structure of IN that was required for its catalytic function, and also showed the inhibitory mechanism of the IN inhibitor. Genetic analysis of IN has revealed additional non-enzymatic roles during viral replication cycles at several steps other than integration. However, the higher order structure of IN that is required for its non-enzymatic functions remains to be delineated. This is the next major challenge in the field of IN structural biology hoping to be a platform for the development of novel IN inhibitors to treat HIV-1 infectious disease.